Impact of adherence to WHO infant feeding recommendations on later risk of obesity and non‐communicable diseases: systematic review. Issue 3 (11th August 2015) - Martin, Anne; Bland, Ruth M.; Connelly, Andrew; Reilly, John J.
Abstract: Adherence to WHO infant feeding recommendations has short‐term benefits and may also help in the prevention of non‐communicable diseases (NCDs). This study reviewed the evidence on whether adherence to all elements of the WHO infant feeding recommendations (comparison group those exclusively breastfed to 6 months, introduced to appropriate complementary feeding from 6 months, with continued breastfeeding to at least 24 months; exposure group characterised by non‐adherence to any of the three recommendations) is associated with reduced risk of later obesity or cardiometabolic disease. The population of interest was children not classified as very low weight (weight‐for‐age z ‐score >−3.0). MEDLINE, EMBASE, Global Health, CINAHL plus, ProQuest Dissertations and Thesis were systematically searched from 2001 to July 2014, manual reference searching of a birth cohort register (http://www.birthcohorts.net/ ) as well as papers identified in the search and selected journals was carried out. The database search yielded 9050 records, 275 English‐language full‐text articles were screened, but no studies were eligible, failing to meet the following criteria: comparison (213); exposure (14); population (3); relevant outcome (5); outcome before 24 months (9); insufficient information provided (30); plus one study was qualitative. Eight studies met the inclusion criterion of exclusive breastfeeding to 6 months, but did not meet the other inclusion criteria. The present study has revealed an important gap in the evidence on NCD prevention, and suggestions for addressing this evidence gap are provided.